Oral hygiene practices and self-perceived halitosis among dental students - Ghufran A Hasan (College of Dentistry/ University of Baghdad, 2014)
Background: Halitosis represents a common dental condition, although sufferers are often not conscious of it. It is common among humans around the world and is usually caused by an accumulation of bacteria in the mouth as a result of gum disease, food, or plaque. This study aimed to determine the prevalence of oral hygiene practices, smoking habits and halitosis among undergraduate dental students and correlate the oral hygiene practices, oral health conditions to the prevalence of self perceived oral malodor. Materials and Methods: Clinical examination of 250 dental students and a self-administered questionnaire were included in this study. A questionnaire was developed to assess the self-reported perception of oral breath, awareness of bad breath, timing of bad breath, oral hygiene practices, caries and bleeding gums, dryness of the mouth, smoking and tongue coating. Results: The results indicated that female students had better oral hygiene practices. Significantly less self-reported oral bad breath (P = 0.000) was found in female dental students (40%) as compared to male (70%). It was found that smoking had statistically highly significant correlation with halitosis (P = 0.000). Presence of other oral conditions such as dental caries and filled carious lesions also showed higher prevalence of halitosis in dental students. Conclusion Oral hygiene practices and oral health conditions are very important factors in halitosis. Females exhibited better oral hygiene practices and less prevalence of halitosis as compared to male students.